2021
DOI: 10.1007/s00162-021-00590-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of separation structure on the dynamics of shock/turbulent-boundary-layer interactions

Abstract: Shock/turbulent-boundary-layer interactions (STBLIs) are ubiquitous in high-speed flight and propulsion applications. Experimental and computational investigations of swept, three-dimensional (3-D) interactions, which exhibit quasi-conical mean-flow symmetry in the limit of infinite span, have demonstrated key differences in unsteadiness from their analogous, two-dimensional (2-D), spanwise-homogeneous counterparts. For swept interactions, represented by the swept–fin-on-plate and swept–compression–ramp-on-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In this interaction, the behavior near each fin exhibits quasi-conical properties, but new features, including a pair of streamwise-oriented vortices, arise in the central interaction region (Schmisseur & Gaitonde 2001). A particularly interesting aspect of the dynamics is the appearance of a band of lower-frequency unsteadiness that is reminiscent of the separation of frequency scales found in 2D SBLI, while not necessarily reflective of the same underlying mechanisms; this is discussed in detail by Adler & Gaitonde (2022). For these interactions, the dependence of nonasymptotic behavior on Mach and Reynolds numbers has not been adequately characterized; these parameters may strongly affect the scaling considerations between ground and flight tests, as well as correspondences between the former and high-fidelity simulations that tend to consider lower Reynolds numbers for computational feasibility.…”
Section: Nonasymptotic Regions: Inceptive and Symmetry-plane Effectsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this interaction, the behavior near each fin exhibits quasi-conical properties, but new features, including a pair of streamwise-oriented vortices, arise in the central interaction region (Schmisseur & Gaitonde 2001). A particularly interesting aspect of the dynamics is the appearance of a band of lower-frequency unsteadiness that is reminiscent of the separation of frequency scales found in 2D SBLI, while not necessarily reflective of the same underlying mechanisms; this is discussed in detail by Adler & Gaitonde (2022). For these interactions, the dependence of nonasymptotic behavior on Mach and Reynolds numbers has not been adequately characterized; these parameters may strongly affect the scaling considerations between ground and flight tests, as well as correspondences between the former and high-fidelity simulations that tend to consider lower Reynolds numbers for computational feasibility.…”
Section: Nonasymptotic Regions: Inceptive and Symmetry-plane Effectsmentioning
confidence: 88%
“…The DF SBLI, which is of increasing interest in hypersonic applications, may be viewed as a compound interaction, resulting from the merger of the two quasi-conical interactions, each generated by one of the opposing fins. Recent efforts (Adler & Gaitonde 2022, Seckin et al 2022 have contributed newer techniques to the classical literature (Zheltovodov 2006, Gaitonde 2015. In this interaction, the behavior near each fin exhibits quasi-conical properties, but new features, including a pair of streamwise-oriented vortices, arise in the central interaction region (Schmisseur & Gaitonde 2001).…”
Section: Nonasymptotic Regions: Inceptive and Symmetry-plane Effectsmentioning
confidence: 99%
“…Solution of the adjoint problem has also been used to compute the wavemaker and propose the physical mechanism of the observed instability scenario. Three-dimensional turbulent separation effects are at the core of the work of Adler and Gaitonde [2], who address the issue of separation arising from shock/boundary layer interactions in three-dimensional configurations of increasing geometric complexity. Using a very large database of experimental and simulation results, these authors catalog unsteady phenomena on the basis of frequency bands and describe qualitative differences between two-dimensional, axisymmetric, open three-dimensional separation in the absence of sidewalls, as well as the effect of the latter on the proposed characterization.…”
Section: Summary Of Articles In This Special Issuementioning
confidence: 99%
“…Abe (2017) continued research of Na & Moin (1998) based on DNS at different Reynolds number (), finding that the scaling law of exhibits good agreement in the APG region with the data of Na & Moin (1998), at low frequencies. Recently, Adler & Gaitonde (2020, 2022) carried out an LES study to investigate the unsteadiness in three-dimensional (3-D) sharp-fin and swept-compression-ramp interactions. They found that flow separation in 3-D interactions is topologically different than two-dimensional (2-D) SBLIs.…”
Section: Introductionmentioning
confidence: 99%